2018
DOI: 10.1371/journal.pone.0199007
|View full text |Cite
|
Sign up to set email alerts
|

Interaction among susceptibility genotypes of PARP1 SNPs in thyroid carcinoma

Abstract: Polymorphisms in DNA repair genes may alter the repair mechanism which makes the person susceptible to DNA damage. Polymorphic variants in these DNA repair pathway genes such as Poly (ADP-ribose) polymerase- 1 (PARP1) have been associated with susceptibility of several types of cancer including thyroid. Many studies have been published on PARP1 gene polymorphisms and carcinogenesis with inconsistent results. The present study was designed to explore the link between the PARP1 polymorphisms and thyroid cancer r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…Indeed, prior studies by our team do suggest that SNPs across different DNA repair pathways – e.g., RAD51 and XRCC3 (HR pathway), CCNH (NER pathway) and MSH6 (MMR pathway) – may be implicated in TC (or, more specifically, DTC) predisposition [14,15,16,17,18]. Such studies add on to prior and subsequent work by other teams [8,12,19,20,21,22,23,24,25] that propose additional markers and reinforce the notion that DNA repair SNPs may contribute to DTC risk. However, besides being scarce, these studies provide only limited information on the impact of the studied SNP in specific subpopulations, e.g., male versus female patients or early-onset versus late-onset DTC.…”
Section: Introductionsupporting
confidence: 51%
See 1 more Smart Citation
“…Indeed, prior studies by our team do suggest that SNPs across different DNA repair pathways – e.g., RAD51 and XRCC3 (HR pathway), CCNH (NER pathway) and MSH6 (MMR pathway) – may be implicated in TC (or, more specifically, DTC) predisposition [14,15,16,17,18]. Such studies add on to prior and subsequent work by other teams [8,12,19,20,21,22,23,24,25] that propose additional markers and reinforce the notion that DNA repair SNPs may contribute to DTC risk. However, besides being scarce, these studies provide only limited information on the impact of the studied SNP in specific subpopulations, e.g., male versus female patients or early-onset versus late-onset DTC.…”
Section: Introductionsupporting
confidence: 51%
“…Considering the specificities of DTC regarding gender distribution and median age at diagnosis [1,2] such detailed analysis could prove useful. Although gene-gene interactions could be of utmost importance in the real context, possibly decisive, they have only seldom evaluated and, when considered [19,20,22,24,26,27], analyses were usually limited to the combined effect of SNPs in the same gene or in genes of the same pathway. DNA repair proteins functionally interact with each other, both within the same DNA repair pathway and across different pathways, establishing ground for additive or even multiplicative effects of different SNPs (irrespective of their pathway) on DNA repair activity and, hence, cancer risk.…”
Section: Introductionmentioning
confidence: 99%
“…Several polymorphisms have been identified in the PARP1 gene; the most studied is T/C‐rs1136410 resulting in a decreased enzymatic activity . Moreover, numerous studies correlate SNPs in PARP1 with susceptibility of diverse malignancies and recently the PARP1 SNP rs1136410 has been associated with NB tumours arising from mediastinum in Chinese population but no association was found with the risk to develop NB.…”
Section: Discussionmentioning
confidence: 99%
“…Such results strengthen the previous findings that these variations may be too weak to impact neuroblastoma risk. To be noted, significant conferring roles of the same BER SNPs to the risk of other cancer types have been detected, such as PARP1 rs1136410 and thyroid cancer [9], OGG1 rs1052133 and Wilms tumor [6], FEN1 rs4246215 and Wilms tumor [6], APEX1 rs1130409 and renal cell carcinoma [10], LIG3 rs1052536 and lung cancer [11]. The different roles of these SNPs in specific cancer types indicated that specific cancer types should be set before interpreting the role of SNPs.…”
Section: Allele Neuroblastoma Patients Cancer‐free Controls Gementioning
confidence: 99%